The colonel's lady on the western frontier : the correspondence of Alice Kirk Grierson - Grierson, Alice Kirk, 1828-1888 (Women in the West., 1989)
The modern woman who tries to juggle private and public roles with equilibrium will discover a spiritual ancestor in Alice Kirk Grierson. The colonel's lady spent most of her life at army outposts on the nineteenth-century western frontier, where she faced the problems of raising a large family while fulfilling the duties of a commanding officer's wife. Fortunately for history, she left a large and extraordinarily candid correspondence, which has now been edited by the author.